Carbon and Nitrogen Metabolism Effects on Eating Quality in Grains of Diverse Japonica Rice Cultivars From the Middle and Lower Yangtze River - Zhongtao Ma; Xi Chen; Jiale Cao; Jianghui Yu; Ying Zhu; Guodong Liu; Fangfu Xu; Qun Hu; Hongcheng Zhang; Guangyan Li; Haiyan Wei (Food and Energy Security)
ABSTRACT The relationship between carbon and nitrogen metabolism and rice eating quality was examined in this study, which focused on four types of japonica rice from the middle and lower reaches of the Yangtze River. These japonica rice varieties were categorized by amylose content and protein content as follows: high amylose content with high protein content, high amylose content with low protein content, low amylose content with high protein content, and low amylose content with low protein content. The study systematically analyzed the carbon and nitrogen metabolism in the grain after flowering and assessed its impact on rice eating quality. Results showed that in japonica rice with similar protein content, low amylose content japonica rice had 5.15%–16.41% lower levels of granule‐bound starch synthase (GBSS) compared to high amylose content japonica rice. Additionally, low amylose content japonica rice displayed 3.84%–23.80% higher levels of soluble starch synthase (SSS), 9.06%–31.05% higher levels of starch branching enzyme (SBE), and 20.27%–53.80% higher levels of starch debranching enzyme (DBE). The synthesis rate of amylose was lower in low amylose‐content japonica rice, while the synthesis rate and content of albumin were higher. In japonica rice with similar amylose content, low protein content japonica rice had 3.41%–12.09% lower levels of nitrogen and 6.94%–20.15% lower levels of glutamate synthetase (GOGAT) compared to high protein content japonica rice. This resulted in a reduced protein synthesis rate and lower contents of glutelin, globulin, and prolamin. Moreover, low‐protein content in japonica rice demonstrated higher levels of SBE and DBE, leading to a decrease in long‐chain amylopectin. Correlation analysis revealed significant interactions between carbon and nitrogen metabolisms, which were closely linked to rice‐eating quality. Carbon metabolism was the predominant factor, followed by nitrogen metabolism, in shaping the eating quality of rice. Carbon metabolism influenced rice‐eating quality by modifying starch synthesis and interacting with nitrogen metabolic pathways, especially those involved in protein synthesis. Low GBSS and elevated SSS, SBE, and DBE levels in grains post‐flowering could reduce amylose synthesis while promoting albumin synthesis, leading to improve the eating quality of japonica rice. Nitrogen metabolism further modifies the taste of cooked rice by adjusting protein synthesis and interacting with carbon metabolism, particularly in starch formation. Reduced nitrogen levels and GOGAT post‐flowering could decrease protein synthesis, notably of glutelin and prolamin, and long‐chain amylopectin in starch, thereby enhancing the eating quality of japonica rice.